High-Density Electroencephalography-Informed Multiband Functional Magnetic Resonance Imaging Reveals Rhythm-Specific Activations Within the Trigeminal Nociceptive Network - Basedau, Hauke; Peng, Kuan-Po; May, Arne; Mehnert, Jan (Frontiers in Neuroscience, 2022)
The interest in exploring trigeminal pain processing has grown in recent years, mainly due to the many pathologies (such as migraine) related to this system. However, research efforts mainly focused on understanding of molecular mechanisms or studying pathological states. Non-invasive imaging studies on the other hand are limited by either spatial or temporal resolution depending on the modality used. This can be overcome by using multimodal imaging techniques such as simultaneous functional magnetic resonance imaging (fMRI) and electroencephalography (EEG). Although this technique has been already applied to neuroscientific research areas and consequently gained insights into diverse sensory systems and pathologies, only few studies applied EEG-fMRI in the field of pain processing and none in the trigeminal system. Focusing on trigeminal nociception, we used a trigeminal pain paradigm, which has been well-studied in either modality. For validation, we first acquired standalone measures with each imaging modality before fusing them in a simultaneous session. Furthermore, we introduce a new, yet simple, non-parametric correlation technique, which exploits trial-to-trial variance of both measurement techniques with Spearman’s correlations, to consolidate the results gained by the two modalities. This new technique does not presume a linear relationship and needs few repetitions per subject. We also show a cross-validation by analyzing visual stimulations. Using these techniques, we show that EEG power changes of theta-band induced by trigeminal pain correlate with fMRI activation within the brainstem, whereas those of gamma-band oscillations correlate with BOLD signals in higher cortical areas.